The Development of Rusunawa Triharjo: How Effective is it in Reducing Slum Settlements? - Dompak, Timbul; Salsabila, Lubna (Asosiasi Ide Bahasa Kepri, 2024)
Rusunawa buildings are constructed in a segregated setting, with distinct sections organized both horizontally and vertically. These units are primarily intended for residential purposes and come with communal facilities, shared amenities, and common land. The objective of the Rusunawa development is to address the issue of slum regions and overcome the constraints of limited land availability. It aims to provide suitable and inexpensive housing options for low-income individuals, specifically those categorized as MBR. The objective of this study is to assess the efficacy of the Rusunawa Triharjo project in mitigating the prevalence of slum settlements in Kulon Progo Regency. The findings of this study indicate that: 1) The intended objective of developing Rusunawa has not been fulfilled by the residents of slum regions in Kulon Progo Regency; 2) The overall goal has not been accomplished due to the community's limited interest in residing in Rusunawa Triharjo.